PERBANDINGAN SEBELUM DAN SESUDAH ADANYA “PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013” DAN PENGARUHNYA TERHADAP PAJAK PERUSAHAAN (STUDI KASUS PADA PT. DBL) - Siti Ratna Sari Dewi (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2019)
AbstractThe purpose of this study is to find out how much the amount of tax issued and whether there is a difference in the amount of tax issued by the company before and after the existence of "PP Number 46 year, 2013 and the influence of the PP Number 46 year 2013" with corporate tax. The nature of this research is qualitative research with a comparative method and descriptive analysis with a case study approach method. Data collection techniques carried out in this study are through primary data, namely data obtained directly from data sources where the research was carried out and secondary data namely data obtained from literature and books that have to do with the problem under study. Through analysis of qualitative descriptive data and quantitative data analysis this research was conducted. And the results of the study show the amount of tax issued before the existence of PP number 46 of 2013 shows no tax payable, whereas after the issuance of the latest regulations the amount of tax incurred has increased. So there are differences in the amount of tax payments incurred due to the issuance of the latest regulations and the influence of the latest regulations on corporate taxes.